Leveraging Academic-Service Partnerships: Implications for Implementing the RWJ/IOM's Recommendations to Improve Quality, Access, and Value in Academic Medical Centers - Xippolitos, Lee Anne (International Scholarly Research Network, 2011)
Transformation of the current healthcare system is critical to achieve improved quality, safety, value, and access. Patients with multiple, chronic health conditions require integrated care coordination yet the current health care system is fragmented and complex. Nursing must play a key role in constructing a system that is value based and patient focused. The Robert Wood Johnson/Institute of Medicine (RWJ/IOM) report on the future of nursing outlines strategic opportunities for nursing to take a lead role in this transformation. Partnerships across academic institutions and health care systems have the potential to address issues through mutual goal setting, sharing of risks, responsibilities, and accountability, and realignment of resources. The purpose of this paper is to present Stony Brook University Medical Center's (SBUMC) academic-service partnership which implemented several of the RWJ/IOM recommendations. The partnership resulted in several initiatives that improved quality, safety, access, and value. It also characterized mutual goal setting, shared missions and values, and a united vision for health care.